2016
DOI: 10.1021/jacs.6b05563
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of Sulfate-Based Diblock Copolymer Nanoparticles within Calcite: Effect of Varying the Surface Density of Anionic Stabilizer Chains

Abstract: Polymerization-induced self-assembly (PISA) offers a highly versatile and efficient route to a wide range of organic nanoparticles. In this article, we demonstrate for the first time that poly(ammonium 2-sulfatoethyl methacrylate)-poly(benzyl methacrylate) [PSEM–PBzMA] diblock copolymer nanoparticles can be prepared with either a high or low PSEM stabilizer surface density using either RAFT dispersion polymerization in a 2:1 v/v ethanol/water mixture or RAFT aqueous emulsion polymerization, respectively. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 57 publications
4
93
0
Order By: Relevance
“…All of the final latexes had pH values between 6.5 and 6.6 which is most probably caused by the P(AMPS) macro‐RAFT agent/surface functionality. Furthermore, unlike other monomer combinations, our emulsion system only yielded spherical NPs, which was also observed by Armes and coworkers when using sulfated polymethacrylate macro‐RAFT agent stabilizers …”
Section: Characterization Data For the Nanoparticles Used In Biologicmentioning
confidence: 89%
See 1 more Smart Citation
“…All of the final latexes had pH values between 6.5 and 6.6 which is most probably caused by the P(AMPS) macro‐RAFT agent/surface functionality. Furthermore, unlike other monomer combinations, our emulsion system only yielded spherical NPs, which was also observed by Armes and coworkers when using sulfated polymethacrylate macro‐RAFT agent stabilizers …”
Section: Characterization Data For the Nanoparticles Used In Biologicmentioning
confidence: 89%
“…We have recently reported synthesis of polyacrylamide coated NPs via RAFT emulsion polymerization, and their use as micro‐RNA vectors and their in vivo biodistribution . Outside of biological applications, Armes and coworkers recently reported the synthesis of sulfated NPs via PISA both in dispersion and emulsion to further understand NP occlusion in calcite and zinc oxide crystals . Due to the highly sulfated nature of the above NPs, we envisaged that similar systems may be able to act as heparin mimics.…”
Section: Characterization Data For the Nanoparticles Used In Biologicmentioning
confidence: 99%
“…Polymeric nanoparticles comprising block copolymers with cationic, 28,34,[36][37][38] anionic 25,39,40 and zwitterionic 41,42 character have been synthesised via PISA. In both dispersion and emulsion-based PISA systems, it has been shown that the morphology is influenced by the charge density of the solvophilic block -if the charge density is too high, only spheres can form due to the strong repulsive forces between the chains on decreasing the curvature of the interface between the core and the continuous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐ionic PMP‐stabilized nanoobjects had little to no effect on the rhombohedral structure of CaCO 3 , while the ionic nanostructures were occluded within the calcite crystals, which exhibited slightly to markedly more curved edges. Sulfated nanomaterials were also considered in the same context . To this aim, an anionic poly(ammonium 2‐sulfatoethyl methacrylate) (polyASEMA; Scheme ) macroRAFT agent was used for both dispersion and emulsion RAFTPISA of BzMA in a 2:1 v/v ethanol/water mixture or pure water, respectively.…”
Section: Functional Complexing Templating and Catalytic Pisa Nanoomentioning
confidence: 99%
“…In nanoparticles obtained by emulsion RAFTPISA, less intraparticular ionic crosslinking occurs, leading to stronger interactions with the growing inorganic crystal and facilitating occlusion (bottom). Adapted with permission . Copyright 2016, American Chemical Society.…”
Section: Functional Complexing Templating and Catalytic Pisa Nanoomentioning
confidence: 99%